Penerapan Problem Based Learning untuk Melatihkan Kemampuan Computational Thinking pada Materi Penokohan Cerita Fiksi - Nawangsih, Retno; Ajeng Wuri Puspita Lusia; Christiyanti Aprinastuti (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Sarjanawiyata Tamansiswa, 2023)
Computational Thinking is one of the competencies added in the Merdeka Belajar Curriculum. Based on observation, SDN Gedongtengen has not implemented the Merdeka Belajar curriculum and will implement the Merdeka Belajar curriculum in the coming academic year so that students need to train computational thinking skills. This research is a descriptive study that aims to describe the application of problem-based learning to train Computational Thinking skills on the characterization material of fictional stories. The instruments used in this study were questionnaires and worksheets and used quantitative and qualitative data analysis techniques. This study involved 25 fourth grade students. The results of this study are the 1) implementation of problem based learning has positive impact of computational thinking skill; 2) the percentage of classical completeness of student learning outcomes reached 96%; 3)the response of students is very high with an average score of 3.5 so it can be concluded that the application of Problem Based Learning on the material characterization of fictional stories has a positive impact on Computational Thinking ability.